DOLLARS AND SENSE : How We Misthink Money and How to Spend Smarter - Ariely, Dan; Kreisler, Jeff; Trower, Matt R. (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2018)
"Shares anecdotal insight into the illogical influences behind poor financial decisions and how to outmaneuver them, covering topics ranging from credit-card debt and household budgeting to holiday spending and real estate sales"--Publisher.
What is money? Don't bet on it ; Opportunity knocks ; A value proposition -- How we assess value in ways that have little to do with value. We forget that everything is relative ; We compartmentalize ; We avoid pain ; We trust ourselves ; We overvalue what we have ; We worry about fairness and effort ; We believe in the magic of language and rituals ; We overvalue expectations ; We lose control ; We overemphasize money -- Now what? Building on the shoulders of flawed thinking. Put your money where your mind is ; Free advice ; Control yourself ; It's us against them ; Stop and think.
Includes bibliographical references (pages 261-268) and index.
Keywords: Finance, Personal; Finance, Personal -- Decision making; Finance, Personal -- Psychological aspects; Consumers -- Attitudes; Consumer behavior -- Psychological aspects